A primer on copper biology in the brain - Alicia R. Lane; Blaine R. Roberts; Christoph J. Fahrni; Victor Faundez (Neurobiology of Disease)
This primer aims to expose scientists who study the brain to the field of copper biology. We briefly discuss key copper homeostasis mechanisms and proteins and place these functions in the context of the brain and neurodevelopment. A small number of key copper genes are explored as representative examples of the importance of this metal to the brain. We show that these genes are expressed throughout the brain and their defects are linked to a diverse array of neurological phenotypes, which we discuss further in the context of several neurological and neurodegenerative diseases associated with dysregulation of copper. This review aims to expose interested scientists to the fundamental roles for copper in the brain, the primary proteins responsible for maintaining copper homeostasis in the brain, and the classic neurological diseases associated with this metal.